Risk-Taking in The Banking Sector: Do Cultural Differences Matter? - Somya M. Eljilany; Ibrahim R. Hegazy; Ahmed F. Elbayoumi (Journal of Accounting and Management Information Systems (JAMIS), 2023)
Research Question- Why the banking sector in some countries experienced more severe panic than the banking sector in other countries? And why some countries recovered faster than others? Motivation- In a response to the global financial crisis, research on the motivation risk-taking or risk-aversion has been increasingly grown to investigate whether culture differences among countries affect the behaviors of individuals inside societies to be risk-taking or risk-aversion? Idea- Test the effect of the four cultural dimensions of Hofstede (2001) i.e. (individualism, uncertainty avoidance, power distance and masculinity) on risk-taking in the banking sector. Data- Our sample consists of 2620 bank-year observations of 262 banks from four countries covering the period from (2011 to 2020) collected from Refinitiv Eikon database. Tools- The statistical techniques used are descriptive analysis, correlation and OLS regression. Findings- We found the effect of national culture on risk-taking is significant for all dimensions. Individualism and masculinity are negatively related to risk-taking and uncertainty avoidance is positively related to risk-taking. For power distance dimension, we found power distance of Hofstede (2001) is significantly and negatively related to risk-taking, while power distance of House et al. (2004) is significantly and positively related to risk-taking. We confirmed our findings with robustness test. Contribution- Our results confirmed the "cushion hypothesis" formulated by Hsee & Weber (1999). We provide evidence on the significant effect of masculinity, long-term orientation and indulgence on bank risk-taking where most previous studies either excluded or found them insignificant. The impact of all cultural dimensions has been confirmed using a small sample of countries.
Keywords: M41; 650; risk taking; individualism; uncertainty avoidance; power distance; masculinity; cushion hypothesis